Evaluating the role of topical steroids as a primary intervention for treatment of phimosis in pediatric age group - Varghese, Vivin Thomas; Mathew, Abraham (International Surgery Journal, 2020)
Background: Phimosis is the inability to completely retract the prepuce, a common cause of anxiety to parents of young boys. It is usually physiological and gradually improves with age. Phimosis is considered a problem when there is fibrotic foreskin and its adherence to the glans making it impossible to expose the glans. Methods: Study was conducted on 82 patients that presented to the surgical Outpatient Department (OPD) at Smt. SCL Hospital, NHL Medical College, Ahmedabad for a period of 2 years between September 2011 to September 2013. Case selection was done by detailed history, clinical examination and followed up regularly at 1 week, 2 week and 1 month in necessary individuals. The treatment consisted of applying a topical steroid (betamethasone 0.05% cream) three times a day. Results: 85% of patients had physiologic phimosis and along with Frenulum Breve the count rose to 91%. Only 9% presented with pathological or acquired phimosis. 51 out of 53 patients who completed the course (96%) achieved success with conservative line of treatment. Only 2 failures were seen (4%). 72.5% of patients responded successfully within 2 weeks of treatment. 27.5% of patients took 1 month of therapy to be successful. Conclusions: The study has shown that a majority (96%) of boys with phimosis can be successfully treated conservatively. Hence, topical steroids might be used as a first-line therapy for phimosis, as a feasible pre-surgery alternative. Surgical interventions should be reserved for recalcitrant phimosis that do not respond to medical administration.